Influence of cage clearance on the heating characteristics of high-speed ball bearings. (January 2017) - Yang, Zhaohui; Yu, Tianxiang; Zhang, Yugang; Sun, Zhongchao
Abstract: This paper presents a five degree-of-freedom (5-DOF) quasi-dynamic model to analyse the relationship between the cage clearance and heating characteristics. First, a mathematical model is constructed for analysing the various heating rates associated with different working conditions, the elasto-hydro-dynamics of the cage is considered. Then, numerical studies are used to validate the precision and efficiency of this method. Second, an experimental system is developed to evaluate the theoretical method. Finally, the various of heating characteristics associated with the guide and pocket hole clearances, are analysed quantitatively. The results show that there is a critical value for both the guide and pocket hole clearance and that the heating is obviously decreased and gradually stabilizes when the clearance exceeds this value. Highlights: Different types of structures formed on pads' surfaces were identified. Non-deformable and deformed primary plateaus were observed on the pads' surfaces. Secondary plateaus can have or not the support of primary plateaus. Friction results are related to the type of structures found on the pads' surfaces.